Arabidopsis ARGONAUTE7 selects miR390 through multiple checkpoints during RISC assembly. (4th June 2013) - Endo, Yayoi; Iwakawa, Hiro‐oki; Tomari, Yukihide
Abstract : Plant ARGONAUTE7 (AGO7) assembles RNA‐induced silencing complex (RISC) specifically with miR390 and regulates the auxin‐signalling pathway via production of TAS3 trans ‐acting siRNAs (tasiRNAs). However, how AGO7 discerns miR390 among other miRNAs remains unclear. Here, we show that the 5′ adenosine of miR390 and the central region of miR390/miR390* duplex are critical for the specific interaction with AGO7. Furthermore, despite the existence of mismatches in the seed and central regions of the duplex, cleavage of the miR390* strand is required for maturation of AGO7–RISC. These findings suggest that AGO7 uses multiple checkpoints to select miR390, thereby circumventing promiscuous tasiRNA production. Arabidopsis ARGONAUTE7 selects miR390 through multiple checkpoints during RISC assembly: Plant AGO7 assembles RISC specifically with miR390 and regulates the auxin signalling pathway. This study shows that AGO7 uses multiple checkpoints and a unique passenger ejection mechanism to select miR390.